Evaluation of the oxidative activity of some free base porphyrins by a chemiluminescence method - MARIANA VOICESCU; RODICA ION; AURELIA MEGHEA (Journal of the Serbian Chemical Society, 2010)
Due to their spectral characteristics, phototoxicity and high affinity for tumour tissues, porphyrins and their derivatives are widely used in modern medicine as contrast agents for cancer diagnostics and as sensitizers in photodynamic therapy, where they kill tumours via enhancement of tumour oxidative stress. The aim of this work was to simulate in vitro the effects caused by oxidation of two free base porphyrins, 5,10,15,20-tetraphenylporphyrin (TPP) and 5,10,15,20‑tetra(4‑methoxyphenyl)porphyrin (TMOPP). The kinetic study was monitored using spectral techniques and chemiluminescence. The effect of both porphyrins on an oxidation process was evidenced using the chemilumi-nescent system, luminal–hydrogen peroxide, in a phosphate buffer at pH 7. It was found that at low concentration, TPP exerts the anti-oxidative effect in the employed chemiluminescent system, while at higher concentrations; its effect is pro-oxidative. TMOPP exerts a pro-oxidant effect, which was more pronounced than TPP. The results are discussed with respect to oxidative stress.